Outcomes in extremely low birth weight (≤500 g) preterm infants: A Western Australian experience. (April 2022) - Athalye-Jape, Gayatri; Lim, Mei'En; Nathan, Elizabeth; Sharp, Mary
Abstract: Background and aim: Extremely preterm (EP) infant survival has significantly improved with advanced neonatal care; however outcomes of infants born with birth weight (BW) ≤500 g remain poor. We aimed to review outcomes of this cohort in our institution. Methods: Retrospective study of all inborn preterm infants born at ≥22 weeks gestational age (GA) and weighing ≤500 g between January 2001–December 2017. Outcomes included short-term morbidity, mortality, neurodevelopmental impairment and growth up to five years of age. Results: Of a total 438 eligible infants, 92 livebirths were admitted to intensive care [median (range) GA: 24 (22−30) weeks; median (IQR) BW: 427.5 (380–499) grams]. Majority [78/92 (84.7%)] were small for gestational age (SGA). In 50% of non-survivors, median (IQR) age of death was 3.5 (1–17.5) days with no late deaths. Medical morbidities were common. Follow-up, including standardised cognitive assessments, was available for 41/46 (89%) infants. At a median age of 5.06 years, 17/41 (41.5%) had moderate-severe disability; non-statistically higher in SGA compared to appropriate for gestational age/AGA (48.6% vs. 33.3%) group. Cerebral palsy (4/41; 10%), deafness needing amplification (1/41; 2.4%) were noted. Weight (32/41, 78%) and height (27/41, 66%) of most children remained at >2 SD below normal. Conclusions: In a cohort of preterm infants weighing ≤500 g at birth, 50% survived after admission to intensive care. Medical morbidities were common and 54% were free from moderate to severe disability at five years. SGA infants had higher rates (48.6%) of moderate to severe disability. Ongoing suboptimal growth in childhood is common. Highlights: Reported survival of preterm neonates with birth weight ≤500grams is variable There is significant variation in long term growth and neurodevelopmental outcomes in this cohort. Clinician approach to parental counselling with an expected fetal birth weight ≤500grams is variable Our results over a sixteen year period showed 50% survival after admission to intensive care. Chronic lung disease was higher and 54% were free from moderate - severe disability at the age of five years.